Keadilan Distributif Dalam Perspektif Ekonomi Islam : Implikasi Filosofis dan Praktis - Anggi Luthfiah Pane; Nurlaila Rachman; Triana Triana (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This paper examines distributive justice within the framework of Islamic economics, exploring its philosophical underpinnings and practical implications. It analyzes the Islamic concept of justice ( adl ), focusing on its application to the distribution of wealth and resources. The study delves into the core principles of Islamic economics, such as zakat, waqf, riba prohibition, and the concept of khalifah (stewardship), and how these contribute to a more equitable distribution of wealth. Furthermore, it investigates the philosophical arguments supporting distributive justice in Islam, drawing upon Islamic jurisprudence and ethical traditions. The paper concludes by discussing the practical challenges and opportunities in implementing distributive justice principles in contemporary economic systems, considering both micro and macro-economic perspectives.